Dynamic Response and Anti-Collapse Analysis of Multi-Column Demolition Mode in Frame Structures - Zhenning Wang; Jianping Yin; Zhijun Wang; Jianya Yi (Buildings)
With the improvement of building safety requirements and the need for risk assessment under extreme conditions such as earthquakes, fires, and explosions, research related to the failure of some key components has received more attention in recent years. The concrete frame is an important and complex research field in structural engineering when analyzing the chain reaction and collapse mode that may occur after the failure or removal of some columns. In order to study the influence of local damage on the stability of the residual structure of a typical frame concrete structure, the dynamic response and collapse resistance of the residual structure of a plane frame structure were analyzed by using the column removal method. Based on LS-DYNA, all working conditions of single column, double column, and multi-column in different demolition positions were designed. By studying the numerical simulation of different adjacent demolition columns and demolition positions, combined with force transmission path analysis and progressive collapse theory, the dynamic response process of damaged structures under different conditions was obtained. Based on the theory of resistance in progressive collapse, the collapse mode and response characteristics of plane frame structures were analyzed. Through the simulation verification of a multi-story frame structure, the dynamic response law under each column removal condition was obtained: with the increase in the number of columns removed, the collapse speed of the building structure and the dynamic response to the remaining structure are enhanced; as the failure column is closer to the center of the structure, the force transmission path of the surrounding structure becomes greater, the resistance provided by the structure increases, the collapse speed becomes slower, the dynamic response range increases, and the progressive collapse of the peripheral column is caused when multiple columns are removed. According to this law, the relationship between the location parameters of the failure column and the vertical displacement and horizontal displacement is established. The results show that the closer the multi-column collapse is to the central area of the structure, the greater the structural response caused by the failure column. Due to the greater constraints and force transmission paths closer to the remaining columns in the center of the structure, it is difficult for the failure structure to eventually cause collapse damage to the central members, and the failure of the secondary external columns close to the external area is more likely to lead to the progressive collapse of the edge structure. The research provides design ideas and insights for the anti-collapse design of frame structures under multi-column demolition conditions. Attention should be paid to the risk of progressive collapse caused by the sub-external area, and this part should be strengthened.